Virtual Reality’s Impact on Tourist Attitudes in Islamic Religious Tourism: Exploring Emotional Attachment and VR Presence - Eman Alkhalifah; Ramy Hammady; Mahmoud Abdelrahman; Alyaa Darwish; Ella Cranmer; Ons Al-Shamaileh; Aikaterini Bourazeri; Timothy Jung (Human Behavior and Emerging Technologies)
This study explores the integration of immersive technologies, specifically virtual reality (VR), to enhance tourist experiences in the rapidly expanding religious tourism sector. Despite VR’s potential, limited research has examined its impact on religious tourism. This study addresses this gap by investigating the role of emotional attachment in influencing VR presence during pre-, on-site, and postexperiences of VR-mediated religious tourism. A quantitative survey was conducted with 201 respondents who participated in VR religious tourism activities. The empirical analysis, conducted using SPSS and AMOS structural equation modeling (SEM), assessed how VR-mediated religious tourism impacts VR presence and tourist attitudes before actual visits. The findings enhance the understanding of VR’s role in shaping Islamic religious tourists’ attitudes and behaviors, revealing the positive influence of VR across different stages of the visit. The study also highlights the significant role of emotional attachment in enhancing previsit intentions, demonstrating its impact on visit intention and emotional connection. This research underscores VR’s potential to improve value creation, influence attitude changes, and enhance user experiences in religious tourism. By extending the existing literature, this study offers new insights into how VR can be effectively utilized to boost tourist engagement and satisfaction in the religious tourism sector.